Large Variability of Dissolved Inorganic Radiocarbon in the Kuroshio Extension of the Northwest North Pacific. Issue 2 (8th January 2018) - Ding, Ling; Ge, Tiantian; Gao, Huiwang; Luo, Chunle; Xue, Yuejun; Druffel, Ellen R M; Wang, Xuchen
ABSTRACT: Radiocarbon ( 14 C) in dissolved inorganic carbon (DIC) was measured for water samples collected from six deep stations in the Kuroshio Extension (KE) region in the northwestern North Pacific in April–May 2015. Vertical profiles of Δ 14 C-DIC indicate that bomb-produced 14 C was present from the surface to ~1500 m water depth. Large variations in Δ 14 C-DIC values (300‰) were observed at 500 m water depth among the stations and the differences were likely controlled by transport and mixing dynamics of different water masses in the region. The major Pacific western boundary currents, such as Kuroshio and Oyashio and regional mesoscale eddies, could play important roles affecting the observed Δ 14 C-DIC variability. The depth profiles of both Δ 14 C-DIC and DIC concentrations can be predicted by the solution mixing model and can be used as conservative tracers of water mass movement and water parcel homogenization in the ocean.